2016
DOI: 10.15713/ins.idmjar.41
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of bleached enamel with novel nutraceutical agents: An in vitro study

Abstract: Background/Purpose: The eff ect of bleaching agents on dental hard tissues was uncertain. Moreover, reverting the side eff ects caused by bleaching using nutraceuticals as remineralizing agents remained uninvestigated. Hence, the aim of this study was to evaluate the eff ect of 22% carbamide peroxide (CP) on the mineral content of enamel and to evaluate the remineralization of bleached enamel after treatment with three diff erent remineralizing agents. Materials and Methods: A total of 30 extracted human maxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, literature is controversial regarding the mineral content of tooth structure following bleaching. Some studies reported a signi cant reduction in both calcium and phosphorous contents after bleaching [9,24] while some others reported no signi cant change in this regard [1,26]. Junior et al [27] reported a reduction in calcium and an increase in phosphorous content after bleaching [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature is controversial regarding the mineral content of tooth structure following bleaching. Some studies reported a signi cant reduction in both calcium and phosphorous contents after bleaching [9,24] while some others reported no signi cant change in this regard [1,26]. Junior et al [27] reported a reduction in calcium and an increase in phosphorous content after bleaching [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many different remineralizing agents have been used to eliminate the adverse demineralizing effects of bleaching agents [8][9][10][11][12][13]. Bioactive glass (BG) is a biocompatible remineralizing agent that can induce cell signaling for tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were decoronated using a double-faced diamond disc attached to a laboratory micromotor, tested for mineral content at three different thirds of the teeth using Energy dispersive X-Ray spectroscopy (14,15).…”
Section: Evaluation Of Mineral Contentmentioning
confidence: 99%